Sistem Informasi â€œAspirasiâ€: Sebuah Bentuk Penanganan Complain Perpustakaan Universitas Gadjah Mada - Nur Cahyati Wahyuni (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2018)
Continuous improvement is the key word for a Library that has already implemented international standard organization (ISO) in its services. The library should pay attention to customer complaint as an input for improvement. UGM Library in coordination with Public Relations of Universitas Gadjah Mada, using Information System